Simplify the following (x + 2/x – 3) (x – 2/x – 3)

(i) (x + 2/x – 3) (x – 2/x – 3)

(ii) (5 – 2x) (5 + 2x) (25 + 4x2)

Answer :

(i) (x + 2/x – 3) (x – 2/x – 3)

It can be written as

= [(x – 3) + (2/x)] [(x – 3) – (2/x)]

= (x – 3)2 – (2/x)2

Expanding using formula

= x2 + 9 – 2 × x × 3 – 4/x2

By further calculation

= x2 + 9 – 6x – 4/x2

So we get

= x2 – 4/x2 – 6x + 9

(ii) (5 – 2x) (5 + 2x) (25 + 4x2)

It can be written as

= [52 – (2x)2] (25 + 4x2)

By further calculation

= (25 – 4x2) (25 + 4x2)

So we get

= 252 – (4x2)2

= 625 – 16x4

More Solutions:

Leave a Comment